EBITDA: sua utilização e interpretação no contexto da qualidade das informações contábeis na visão dos analistas de mercado de capitais - Momose, Carlos Isao (2009)
EBITDA ( earnings before interest, taxes, depreciation and amortization ) is a non-accounting indicator. Its first records appeared in the decade 60, but became well-known only as from the decade 80 with the development of mergers and acquisitions occurred at the time. It was a way of how to measure companies with high amounts of amortizations and depreciation. At present the use of EBITDA is largely widespread in the capital market, but its efficacy and preparation are constantly called into question. The problem of the research arose therefrom. The main purpose of such research is to clarify, by means of the conceptual structure of the accountancy, more specifically by the qualitative characteristics of the accounting information, the reason of the use of EBITDA. The secondary purposes are: to identify amounts relating to EBITDA, its identity as an operational cash flow, tendency of the future and comparative research of indicators. To structure the research, a questionnaire and structured interviews were adopted as an instrument. In the questionnaire 50 valid answers were obtained and 3 participants, all of them acting directly or indirectly in the capital market, were interviewed. With the results obtained from the research, it can be concluded that: the comparability is the major quality of EBITDA s information; it is very good as an operational indicator; it is not identified as an operational cash flow and tends to continue to be used in the future